Quasi-Grammian Solutions of the Generalized Coupled Dispersionless Integrable System - Haider, B.; Hassan, M. (Symmetry, Integrability and Geometry: Methods and Applications, 2012)
The standard binary Darboux transformation is investigated and is used to obtain quasi-Grammian multisoliton solutions of the generalized coupled dispersionless integrable system.